E-learning satisfaction during Covid-19 pandemic lockdown: analyzing key mediators - Nurhizam Safie Mohd Satar; Omkar Dastane; Azizan Morshidi (Mashhad: Behzad Hassannezhad Kashani, 2021)
An ample of studies have recently been conducted to explore and analyze the predictors of students’ e-learning satisfaction (ELS) during the COVID 19 pandemic lockdown. However, research is scarce on investigating mediating roles of key aspects, such as students’ learning stress (SLS) and students’ willingness to learn (SWL). This research intends to investigate mediating effect of SLS and SWL in relationships among selected IT characteristics factors and ELS during lockdown enforced to curb the COVID 19 pandemic. Selected factors of IT characteristics are IT complexity, IT pace change and IT presenteeism. The data was collected through online questionnaire survey on 470 students in Malaysia selected by employing the convenience sampling during the Movement Control Order period when universities and colleges shifted to online learning platforms. The data was then subjected purification, assessment of normality and reliability. Thereafter, confirmatory factor analysis and validity assessment were conducted. Finally, hypotheses were tested by formulating structural equation model using IBM SPSS AMOS 24.0. The mediation effects were tested by developing parallel mediation structural model. The findings show that SLS fully mediates relationship between IT pace change and ELS. Students’ willingness to study fully mediates relationships between IT presenteeism and IT pace change with ELS.